Experience psychology - King, Laura A. (New York ; London : McGraw-Hill Higher Education ; McGraw-Hill, 2010)
Do you want your students to just take psychology or to experience psychology?
Includes bibliographical references and index
PSYCH
Keywords: Psychology -- Textbooks